Synthesis of plant-soil feedback effects on eastern North American tree species: implications for climate-adaptive forestry - Refsland, Tyler K.; Adams, Bryce; Bronson, Dustin; Kern, Christel C.; Marquardt, Paula; McGraw, Amanda M.; Royo, Alejandro A.; Miesel, Jessica R. (Frontiers in Ecology and Evolution, 2023)
Climate change represents an existential threat to many forest ecosystems because tree populations are often adapted to local climate means and variability. If tree populations cannot migrate or adapt, they risk becoming increasingly maladapted with climate change. This emerging mismatch underscores the need for climate adaptive management techniques, such as assisted migration of tree species, to help mitigate climate change impacts on forest ecosystems. Although biotic and abiotic factors are known to constrain tree establishment success, the extent to which they may determine the success of assisted migration plantings is poorly understood. Thus, defining the extent to which trees affect -- and in turn are affected by -- local soil environments and microbial communities (i.e., plant-soil feedbacks; hereafter PSFs) remains important for guiding effective climate-adaptive forest management. Our objectives were to synthesize the current state of knowledge about the direction and magnitude of PSF effects on temperate tree species of eastern North America, and to identify key hypotheses important for guiding future research. To accomplish these goals, we conducted a meta-analysis of 26 peer-reviewed publications that addressed our criteria. Our compiled database included 61 tree species and was composed primarily of short-term greenhouse experiments that studied PSF effects by manipulating soil biota in three ways: (1) soil was previously inoculated by a conspecific or heterospecific tree species (i.e., home versus away), (2) soil was live or sterilized, or (3) soil was untreated or treated with fungicide. We found that PSF had significant effects on tree growth, with the direction and magnitude of PSF strongly dependent on tree mycorrhizal guild. Arbuscular mycorrhizal tree species grown in live or home soils grew 13-33% less than those in sterile or away soils, while ectomycorrhizal tree species grew 11-44% more in live or home than sterile or away soils. PSF effects were associated with several plant functional traits, including specific leaf area, tissue nitrogen, and specific root length. We provide suggestions on incorporating PSFs into assisted migration trials and outline key knowledge gaps for future research. Our synthesis of context-dependent effects of PSF on tree performance will help inform management decisions involving assisted migration.